SMART VILLAGE DEVELOPMENT STRATEGY IN SUKAPURA VILLAGE, INDONESIA - Agung Nurrahman (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2024)
Smart villages are deemed capable of addressing fundamental issues in rural areas; however, scientific publications on smart village development strategies remain scarce. This study aims to scrutinize the smart village development strategy in Sukapura Village, Indonesia. This research method is qualitative, using SOAR analysis and litmus tests. The results showed that there were 13 strategic issues that had been analyzed through SOAR analysis and then after the litmus test, the 7 most strategic issues were obtained. The research concludes that the Smart Village Development Strategy in Sukapura Village, Indonesia, can be effectively pursued through a 4-pronged approach: 1) regulation measures, 2) facilitation, 3) collaboration, and 4) socialization. Overall, these strategies involve drafting regulations, providing facilitation and training, collaborating with academics and other stakeholders, and utilizing social media for community involvement. Keywords: Smart Village, Smart Village Strategy, Smart Village Development Strategy